An analysis of net-outcome contracting with applications to equity-based compensation - Christian Hofmann; Steven Huddart; Thomas Pfeiffer (Review of Accounting Studies, 2022)
Options, restricted stock, bonuses tied to total shareholder return, and similar equity-based compensation contracts stipulate payments that depend on stock price. Any such contract is a function of shareholder value net of the compensation payment, because stock price (1) is proportional to this net value or "net outcome" and (2) anticipates compensation-related payments and dilution. The net outcome, in turn, is reduced by the payment and so depends on the contract. Standard moral hazard analyses, wherein contractual payments are based on the gross outcome before any payment to the agent, overlook this dependency. We characterize the optimal net-outcome contract, describe its shape and pay-for-performance sensitivity, contrast it with the optimal gross-outcome contract, and discuss implications for equity-based compensation arrangements.
Keywords: D86; J33; M41; 650; Dilution; Moral hazard; Team compensation; Optimal contracting; Pay-for-performance sensitivity; Stock option